Mathematical representation: A bibliometric mapping of the research literature (2013–2022) - Putra, Fredi Ganda; Lengkana, Dewi; Sutiarso, Sugeng; Nurhanurawati, Nurhanurawati; Saregar, Antomi; Diani, Rahma; Widyawati, Santi; Suparman, Suparman; Imama, Khoirunnisa; Umam, Rofiqul (IKIP Siliwangi and I-MES, 2024)
Mathematical representation ability is an essential skill for students to understand mathematical concepts. Many studies have been conducted regarding this ability, but it is necessary to map existing research to provide a clearer picture of future research topics. This study aims to provide a bibliometric review of trends using mathematical representation skills in mathematics teaching research. The method in this study is bibliometric analysis, which aims to analyze and classify bibliographic material by presenting representative summaries of the literature in the Scopus database. The search was carried out using the keyword